If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) = 6(x + -10) Reorder the terms: 3(4 + x) = 6(x + -10) (4 * 3 + x * 3) = 6(x + -10) (12 + 3x) = 6(x + -10) Reorder the terms: 12 + 3x = 6(-10 + x) 12 + 3x = (-10 * 6 + x * 6) 12 + 3x = (-60 + 6x) Solving 12 + 3x = -60 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 12 + 3x + -6x = -60 + 6x + -6x Combine like terms: 3x + -6x = -3x 12 + -3x = -60 + 6x + -6x Combine like terms: 6x + -6x = 0 12 + -3x = -60 + 0 12 + -3x = -60 Add '-12' to each side of the equation. 12 + -12 + -3x = -60 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = -60 + -12 -3x = -60 + -12 Combine like terms: -60 + -12 = -72 -3x = -72 Divide each side by '-3'. x = 24 Simplifying x = 24
| 51=y+7 | | 264-x=182 | | 6+12n-5=5n+46-2n | | y=4x^2+25x-21 | | 1.2x+-4y=28 | | 3x+4=10x-6 | | 18/x-4=10/x | | X/7+1=-1 | | 1/3x+y=6 | | X-a+4=ax+2b-6 | | 1/2(4a+10)=2+ | | 9=5x-4x+5 | | 4ab+9=c | | -1.5(a+1)=0.5(a-9) | | -1.5(a+1)=0.5(a-9) | | 2/3*8=51/3 | | Y=2(-1/3)+7 | | v-2/2=4/3 | | -3.2=[8p] | | -4a/9-6=4 | | -3(16+3)+4(24+1)=43 | | 1/3t-4/3=-5/4t-3/2 | | 12/5=4w | | 2/3*8 | | 2(a+4)/2=14 | | 3x-27=14 | | 4.5=5t | | -2/7u+5/4=-3/8u+1/4 | | 0.5x+3=0.12x-2 | | 15.4r=61.6 | | 6(v+3)=72 | | 2z+9z=4z+45+2r |